Undifferentiated Embryonal Sarcoma of the Liver: An Enigma of Diagnosis - Affirul Chairil Ariffin; Firdaus Mohd Hayati; Nornazirah Azizan; Zamri Zuhdi; Azlanuddin Azman; Hairol Azrin Othman; Razman Jarmin (2018)
A 20-year-old man presented with peritonitis requiring emergency laparotomy. He was found to have a huge liver abscess on the right lobe. Open drainage was performed but the abscess was persistently unresolved upon follow up. Computed tomography (CT) revealed a solid liver lesion with raised Ca 19-9. Right hepatectomy was subjected and histology was consistent with a rare and aggressive case of embryonal sarcoma of the liver. Despite oncologic resection, he developed local recurrence and succumbed to death in 6 month postoperatively. We describe a unique aetiology of liver abscess with literature reviews of undifferentiated embryonal sarcoma of the liver.